2015
DOI: 10.1073/pnas.1413127112
|View full text |Cite
|
Sign up to set email alerts
|

Dried whole-plant Artemisia annua slows evolution of malaria drug resistance and overcomes resistance to artemisinin

Abstract: Pharmaceutical monotherapies against human malaria have proven effective, although ephemeral, owing to the inevitable evolution of resistant parasites. Resistance to two or more drugs delivered in combination will evolve more slowly; hence combination therapies have become the preferred norm in the fight against malaria. At the forefront of these efforts has been the promotion of Artemisinin Combination Therapy, but despite these efforts, resistance to artemisinin has begun to emerge. In 2012, we demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
85
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(90 citation statements)
references
References 59 publications
(63 reference statements)
3
85
1
1
Order By: Relevance
“…The content of artemisinin in the capsules containing A. annua L. leaf powder is approximately 0.1%; hence, it can be estimated that 1-3mg of artemisinin was administered daily. As the capsules only contain leaves, the possibility of the sub-therapeutic doses to generate resistance in malaria is low 29 . The advantage of A. annua L. powder, in comparison to the tea preparation, is that the powder may supply all the molecules present in the plant, particularly the polysaccharides, coumarins, saponins, phytosterols, essential oils, polyphenols, and flavonoids 30 .…”
Section: Discussionmentioning
confidence: 99%
“…The content of artemisinin in the capsules containing A. annua L. leaf powder is approximately 0.1%; hence, it can be estimated that 1-3mg of artemisinin was administered daily. As the capsules only contain leaves, the possibility of the sub-therapeutic doses to generate resistance in malaria is low 29 . The advantage of A. annua L. powder, in comparison to the tea preparation, is that the powder may supply all the molecules present in the plant, particularly the polysaccharides, coumarins, saponins, phytosterols, essential oils, polyphenols, and flavonoids 30 .…”
Section: Discussionmentioning
confidence: 99%
“…44 Because the pathogenesis of DN is multi-etiological, crude extracts of plants may be more useful because they are a natural cocktail of various phytomolecules, all of which could act synergistically to achieve their therapeutic goal. [9][10][11] The present study paves a path for further studies with this plant material to develop a drug for the treatment of DN, which usually leads to ESRD, a major cause of premature death in diabetic patients. Meanwhile, the findings of the present study support the existing clinical use of P. tuberosa in Ayurveda and suggest the need for observational studies of P. tuberosa as a food supplement to manage DN.…”
Section: Discussionmentioning
confidence: 99%
“…Herbal medicines are natural cocktails of secondary metabolites and there is considerable experimental data indicating their benefits over single isolated phytochemicals. [9][10][11] In experimental animal models, DN is defined as increased urinary albumin excretion, with low creatinine clearance, a decreased glomerular filtration rate, and high serum urea and creatinine levels. Structural changes in animal models of DN include glomerulosclerosis, thickening of the basement membrane, and excessive accumulation of eosinophilic casts (EC) and extracellular matrix (ECM).…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have shown that even these treatments lead to a high recrudescence rate and the increased potency of the plant mixture is still not enough to cure the disease. A report by Elfawal et al (2015) discusses the possibility of using the entire A. annua plant in treatment of Malaria, rather than pharmaceutically produced artemisinin. With the growing resistance to ACT, Elfawal and colleagues propose that the success of whole plant treatment in rodent models show that its use in humans should be explored.…”
Section: Artemisininmentioning
confidence: 99%